Interfaith Marriage in the Perspective of Islamic Legal Sociology - Alendra, Deni; Arisman (El-Rusyd, 2025)
Interfaith marriage continues to generate debate in plural societies, particularly in Indonesia, where religion constitutes the basis for the legal validity of marriage. This study aims to analyze the phenomenon of interfaith marriage from the perspective of Islamic legal sociology by highlighting the relationship between religious norms, state law, and social realities. This research employs a qualitative approach using a normative–empirical method through content analysis of Islamic legal sources, statutory regulations, and relevant sociological literature. The findings reveal a tension between normative legal frameworks and social practices, which has led to the emergence of various societal strategies in responding to existing legal restrictions. This article concludes that interfaith marriage is not merely an issue of normative Islamic jurisprudence, but also a social phenomenon that requires a contextual approach to ensure that Islamic law remains responsive to societal dynamics without losing its fundamental value orientation.